Radon exposure and oropharyngeal cancer risk. Issue 1 (1st December 2015) - Salgado-Espinosa, Tania; Barros-Dios, Juan Miguel; Ruano-Ravina, Alberto
Highlights Radon exposure might be linked with oral and pharyngeal cancers. The available literature does not show an association between radon exposure and these tumours. This association does not appear to exist neither for miners nor for general population. No study has been found analysing directly this association. Such studies are encouraged.